Garbage smells! No more with odourepel / Nemisha Suppiah ... [et al.] - Suppiah, Nemisha; Kunalan, Sonisha; Kumar, Kaarthikhesan Suria; Mohan, Veran; Anendan, Thenesha (2020)
In general, the negative image of garbage comes from the fact often smells when microorganisms grow on food waste. It contains decaying, putrescible materials such as meat or vegetables or diapers. As meat decays, it attracts bacteria that feast on the amino acids in the meat's proteins. Vegetable's rot and slowly liquefy as microbes attack the vegetables' cell structure and the fermenting liquids warm up the garbage bag. The odours from the decomposition process are a variety of goodies with nasty sounding names. After all, who wants to invite "cadaverine" or "putrescine" over for dinner? Although these smells are obnoxious, they do not pose a health threat. However, the rats and flies attracted by rotting garbage do. These "vectors" spread diseases that can be serious to humans if they get into our food supplies. The object of this invention is to treat the garbage by absorbing the discharged fluid and to repel the bad odour. The use of waste materials such as coco peat, corn cob and coffee ground in the muslin cloth pack is invented for this purpose. This ODOURepel had received good feedback from the household residents. They feel relief from the bad odour of their garbage. This product is aligned with the green technology, where it is potentially important concept which plays a role to achieve the global sustainable development.